GAMBARAN PENATALAKSANAAN MOBILISASI DINI OLEH PERAWAT PADA PASIEN POST APPENDIKTOMY DI RS PKU MUHAMMADIYAH GOMBONG - hesti marlitasari; Basirun -; Ning Iswati (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2010)
Early mobilization is an important thing to do because it can swit the blood flow, prevent post operation complication, prevent contracture and accelerate the wound healing process. Commonly, the patients are still afraid of doing early mobilization without the nurse companion and guidance. They afraid of the effect that the wound from the surgery will damage by the mobilization but in fact the ealy mobilization for post operation patients theoretically is really good for vascularization and wound healing process. The Objective of the research is to find out description of early mobilization application system by nurses for appendectomy post operation patients in PKU Muhammadiyah Gombong Hospital. It is a non experimental research that used descriptive observational design with Cross sectional approach. The research finding showed description of early mobilization application system by nurses for appendectomy post operation patients in PKU Muhammadiyah Gombong Hospital 17 respondents (62,96%) were in good category and 7 respondents (25,93%) were in good enough category. There were 19 nurses who had done good early mobilization for the appendectomy post operation patients in PKU Muhammadiyah Gombong Hospital. Keywords : appendectomy, the early mobilization